Worldwide Development Tendency of International Tourism - Kilichova O. Z.; Isomiddinov Sh. S. (International Journal on Economics, Finance and Sustainable Development, 2022)
This article discusses the economic and social importance of tourism, its relationship with other economic sectors, and development trends. Economic indicators and statistics were analyzed, and tourism recovery situations and forecasts were analyzed throughout the world.